2021
DOI: 10.1155/2021/7211055
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy of Carbon Dioxide Laser Combined with ALA Photodynamics in the Treatment of Condyloma Acuminatum

Abstract: ’Purpose. To observe the clinical efficacy and safety of carbon dioxide laser combined with ALA photodynamics in the treatment of condyloma acuminatum. Method. A total of 211 patients with condyloma acuminatum admitted to our hospital from April 2018 to June 2021 were selected as the observation object. They were divided into the intervention group (CO2 laser combined with ALA photodynamic therapy, 125 cases) and conventional group (CO2 laser treatment, 86 cases), and the efficacy and incidence of adverse reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recurrence refers to the occurrence of new warts within 2.0 cm of the original wart site or the original wart site within 6 months after the removal of wart body treatment [ 11 ]. The histopathological examination wart body is positive, and the history of repeated infection is excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Recurrence refers to the occurrence of new warts within 2.0 cm of the original wart site or the original wart site within 6 months after the removal of wart body treatment [ 11 ]. The histopathological examination wart body is positive, and the history of repeated infection is excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…ALA-PDT therapy is a popular therapy in recent years. In addition to treating genital warts, this method has a certain therapeutic effect on skin precancerous lesions, malignant tumors, acne and atrophic lichen sclerosis and it is not easy to cause drug resistance in the process of killing pathogenic microorganisms [11,12] . ALA-PDT therapy is mainly based on the principle that photosensitizers produce destructive substances under the irradiation of specific wavelengths of light.…”
mentioning
confidence: 99%